Seren Taun dan Dinamika Sosial: Akulturasi Tradisi Agraris dalam Manuskrip Meteumeuyan - Supendi, Usman; Sopiah, Eva (UPT Publikasi Ilmiah, 2025)
In the existence of a cultured society, various customs and traditions emerge as a result of the knowledge available. This also applies to agrarian communities. Indonesia itself is the largest agrarian country ever recorded in Asian history, particularly in the agricultural sector of rice cultivation. For hundreds of years, Indonesia has been one of the largest rice-producing countries, especially in Parahyangan or West Java. The Sundanese people in this region have practiced agrarian customs for centuries. One of the traditions that remains preserved is Seren Taun, a traditional ceremony held to celebrate the harvest. This ceremony is still practiced and maintained in traditional villages such as Kanekes Baduy, Ciptagelar in Sukabumi, Cigugur in Kuningan, and other customary villages. Interestingly, Seren Taun is not only found in traditional villages but can also be observed in remote villages. Examples include Bojongsari and Sukamaju villages in Nyalindung District, Sukabumi Regency, where this tradition is still upheld with distinct characteristics. The Seren Taun ceremony in these villages differs significantly from the version practiced in traditional communities. This ceremony has undergone various forms of acculturation, whether in terms of social culture or religion. With the discovery of the Meteumeuyan Manuscript, which serves as a customary guide or is also called ririmbon panen, this study attempts to reveal the contents of the manuscript. However, with all the traditional rules attached to it, Seren Taun tends to preserve agrarian traditions across generations, ultimately limiting openness to innovation and social change.